Clinically relevant exaggerated pharmacodynamic response to dual antiplatelet therapy detected by Thromboelastogram ® Platelet Mapping™ - Kenneth N Hiller (Wolters Kluwer Medknow Publications, 2016)
Dual antiplatelet therapy (DAPT) is the standard of care for primary and secondary prevention strategies in patients with coronary artery disease after stenting. Current guidelines recommend that DAPT be continued for 12 months in patients after receiving drug eluting stents. Approximately 5% of these patients will present within this 12-month period for noncardiac surgery. This case report describes a clinically relevant exaggerated pharmacodynamic response to DAPT detected by preoperative assessment of platelet function. Based on the clinical history and physical exam and subsequent lab results, a general anesthetic was performed rather than a spinal anesthetic and the surgical procedure was changed. An exaggerated pharmacodynamic response to DAPT poses its own set of risks (unexpected uncontrolled bleeding, epidural hematoma following neuraxial block placement) that point-of-care aggregation testing may decrease or mitigate by altering clinical decision making. If the clinical history and physical exam reveal possible platelet dysfunction in patients receiving DAPT, preoperative platelet function testing should be considered.